Platelet Rich Plasma Versus Corticosteroid Injections in Treatment of Knee Osteoarthritis - Zeyad Buahlaika,; Ahmad Saad,; Sanad Younes, (AlQalam Journal of Medical and Applied Sciences, 2024)
This study seeks to assess and compare the impact and functional outcomes of platelet-rich plasma and corticosteroid injections in individuals with knee osteoarthritis. In this prospective study, sixty randomly selected patients diagnosed with mild to moderate knee osteoarthritis were included. The patients underwent treatment with either platelet-rich plasma or corticosteroid injection. The assessment of patients was conducted during a follow-up period ranging from six months to one year, utilizing the visual analog scale and the Knee Injury and Osteoarthritis Outcome Score. Written informed consent was obtained from each participant included in the study. This study revealed that patients treated with PRP injections demonstrated favorable outcomes, including an improved range of motion and earlier return to activity, when compared to those treated with corticosteroid injections. Based on clinical scoring using the Knee Injury and Osteoarthritis Outcome Score (KOOS), the mean result for PRP injection recipients was 83.5, whereas for corticosteroid injection recipients, it was 61.8. While both PRP and intra-articular corticosteroid injections prove effective in alleviating pain and enhancing activities of daily living, this study highlights that patient receiving PRP injections exhibited superior outcomes. Specifically, they experienced better pain relief, improved range of motion, and a quicker return to activity compared to those treated with corticosteroid injections. تسعى هذه الدراسة إلى تقييم ومقارنة التأثيرات والنتائج الوظيفية لحقن البلازما الغنية بالصفائح الدموية وحقن الكورتيكوستيرويد لدى الأفراد المصابين بالتهاب مفاصل الركبة. في هذه الدراسة الاستباقية، تم اختيار ستين مريضًا بشكل عشوائي تم تشخيصهم بخشونة مفاصل الركبة الخفيف إلى المتوسط. خضع المرضى للعلاج إما بحقن البلازما الغنية بالصفائح الدموية أو حقن الكورتيكوستيرويد. تم تقييم المرضى خلال فترة متابعة تتراوح بين ستة أشهر وسنة باستخدام مقياس التناظر البصري ودرجة إصابة الركبة ونتائج خشونة المفاصل العظمية. أظهرت هذه الدراسة أن المرضى الذين عولجوا بحقن البلازما الغنية بالصفائح الدموية أظهروا نتائج إيجابية، بما في ذلك تحسن في نطاق الحركة والعودة المبكرة إلى النشاط مقارنةً بالمرضى الذين عولجوا بحقن الكورتيكوستيرويد. بناءً على التقييم السريري باستخدام درجة إصابة الركبة ونتائج التهاب المفاصل العظمي، كان متوسط النتيجة لمتلقي حقن البلازما الغنية بالصفائح الدموية 83.5، في حين كان 61.8 لمتلقي حقن الكورتيكوستيرويد. في حين أن كلا من حقن البلازما الغنية بالصفائح الدموية وحقن الكورتيكوستيرويد داخل المفصل أثبتت فعاليتها في تخفيف الألم وتحسين الأنشطة اليومية، تسلط هذه الدراسة الضوء على أن المرضى الذين تلقوا حقن البلازما الغنية بالصفائح الدموية أظهروا نتائج متفوقة. بشكل خاص، شعروا بتخفيف أكبر للألم، وتحسن في نطاق الحركة، وعودة أسرع إلى النشاط مقارنةً بالمرضى الذين عولجوا بحقن الكورتيكوستيرويد